2010
DOI: 10.1051/forest/2010034
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration niche of the Canarian juniper: the role of adults, shrubs and environmental conditions

Abstract: Abstract• Canarian Juniper woodlands, now very scarce, are rich in endemic and endangered plants. However, many aspects of juniper regeneration are almost unknown.• This paper relates occurrence and abundance of recruits of Juniperus turbinata ssp. canariensis to (1) small-scale soil characteristics; (2) vegetation cover; and (3) distance to conspecific adults in two contrasting juniper stands in the eastern mountains of Tenerife. We used non-parametric classification trees and generalised linear models (GLM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
2
12
0
8
Order By: Relevance
“…Abiotic constraints influencing seedling survival have been shown to be the main driving force of recruitment in relict populations of several "non-Mediterranean" species under Mediterranean climate (Castro et al 2004;Pulido et al 2008;Mendoza et al 2009;Sanz et al 2009;Otto et al 2010). More generally, strong sensitivity of demographic processes to drought stress has been pointed out for many tree species growing under Mediterranean climate (Brèda et al 2006).…”
Section: Synthesis: Recruitment and Conservation Of Southern Periphermentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic constraints influencing seedling survival have been shown to be the main driving force of recruitment in relict populations of several "non-Mediterranean" species under Mediterranean climate (Castro et al 2004;Pulido et al 2008;Mendoza et al 2009;Sanz et al 2009;Otto et al 2010). More generally, strong sensitivity of demographic processes to drought stress has been pointed out for many tree species growing under Mediterranean climate (Brèda et al 2006).…”
Section: Synthesis: Recruitment and Conservation Of Southern Periphermentioning
confidence: 99%
“…These predictions, derived from Bioclimate Envelope Models, rely on the assumption that factors other than climate are not influential at the relevant scale (Hampe 2004a). However, predictions concerning range boundaries may not reflect actual species distributions if species are able to find local refuges buffering latitudinal shifts at the eroding edge (Castro et al 2004;Camarero et al 2005;Truong et al 2007;Pulido et al 2008;Mendoza et al 2009;Sanz et al 2009;Otto et al 2010), or if they are not able to disperse to predicted climatically suitable areas at the leading edge (Svenning and Skov 2007). In the case of eroding edges, where populations are expected to be in decline, knowledge of the factors limiting tree recruitment and of the ability to track environmental change through dispersal is essential for understanding the persistence of populations (Hampe and Petit 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a lack of comparative studies of richness patterns using the same plot size for all main ecosystems of the island, we can show that the remaining juniper woodland patches represent high local biodiversity spots within the recognized regional biodiversity hotspot of the Canarian Archipelago. With respect to perennial vascular plants, and depending on plot size (100-400 m 2 ), mean richness values per plot of 12-19 species were recorded for the succulent scrub, 21.3 for juniper woodlands (present study), 10-15 for the laurel forest, 4-8 for the pine forest and 3-6 for the summit scrub (Fernández-Palacios 1987;Otto et al 2001;Otto 2003;Otto et al 2010). This would indicate a hump-shaped distribution of habitat richness along the elevation gradient on Tenerife with maximum richness at mid-altitudes, i.e.…”
Section: Species Richnessmentioning
confidence: 52%
“…This is also justified by the findings that J. turbinata ssp. canariensis has a low regeneration capacity on this island due to low growth rates, dispersal difficulties and regeneration niches that depend on favorable environmental conditions and structural characteristics of the vegetation (Fernández-Palacios et al 2008;Otto et al 2010). In most of the juniper patches studied in the drier South of the island, no regeneration of the Canarian juniper and rarely fruit production have been observed (Otto and Barone, unpubl.…”
Section: Consequences For Conservationmentioning
confidence: 99%
“…Juniperus forest in the Nepal Himalayas is under threat due to high anthropogenic pressure (e.g., destructive practices, such as over-harvesting of leaves for incense and slash-burning to harvest its wood) as well as harsh climatic conditions. Studies carried out in other parts of the world have shown that the principal ecological problems in junipers are related to low production of viable seeds (Juan et al, 2003;Otto et al, 2010). Juan et al (2003) assessed viability in J. oxycedrus which showed difficulties in seed germination because of harsh cold climate.…”
Section: Variation In Leaf Biomass and Fruit Output Of Juniperus Indimentioning
confidence: 99%